Indonesian Coffee Export Analysis to Germany From 1990 to 2019 - Winingsih, Titis Rahayu; Septiani, Yustirania (AFEBI Economic and Finance Review, 2022)
Export is the activity of selling goods abroad, one of Indonesia's main export commodities is coffee. Germany is the highest coffee consuming country in the European region, this makes Germany a potential market for Indonesian exports. This study was conducted to determine the factors that affect the volume of Indonesian coffee exports to Germany using quantitative methods and secondary data types in the form of time series from 1990 to 2019. The data sources were obtained from the Directorate General of Plantation (Ditjebun), the Central Statistics Agency ( BPS), World Bank, International Coffee Organization (ICO). Multiple regression model with ECM approach was used to analyze the data. The results of this study indicate that in the long and short term coffee production, German GDP and world coffee prices have an insignificant negative effect on coffee export activities, but in the short term the coffee production variable has a positive and insignificant effect.